Microstructural evaluation of an asymmetrically rolled and recrystallized 3105 aluminum alloy - Saulo Brinco Diniz; Emanuel Alejandro Benatti; Andersan dos Santos Paula; Raúl Eduardo Bolmaro; Luis Celso da Silva; Bruna Godoi Meirelles (Journal of Materials Research and Technology, 2016)
This study evaluates the influence of the structural changes promoted by a solution heat treatment (ST) on recrystallization and grain growth during annealing of the 3105 Al alloy subject to asymmetric rolling. Optical Microscopy, Scanning Electron Microscopy (SEM)/X-Ray Energy Dispersive Spectroscopy (EDS), X-Ray Diffraction (XRD), dilatometric analysis and Vickers hardness tests were used to evaluate the microstructural and mechanical properties. The influence of solution heat treatment on grain growth kinetics could not be evaluated because of incomplete recrystallization due to the chosen annealing parameters.